2018
DOI: 10.7596/taksad.v7i4.1809
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Future Behaviors among Disabled Children: An Empirical Study on Schoolchildren

Abstract: The problem of socio-psychological adaptation and socialization among the children with developmental disabilities in society is actively studied by researchers. As the resource for the successful socialization of children with developmental anomalies, they regard the ability to anticipate that allows children to plan their own actions, avoid psychotraumatic situations and to prevent behavioral disorders and deviant behavior. The purpose of this study was to identify the specifics of future event prediction by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…Similar results among children of primary school age were published in the studies by Rozental, Akhmetzyanova, and Artemyeva (2018) and Guralnick (2010): children with visual disorders showed playful behaviour which had mostly individually-searchful nature, and such children did not to strive to play team games.…”
Section: Resultssupporting
confidence: 83%
“…Similar results among children of primary school age were published in the studies by Rozental, Akhmetzyanova, and Artemyeva (2018) and Guralnick (2010): children with visual disorders showed playful behaviour which had mostly individually-searchful nature, and such children did not to strive to play team games.…”
Section: Resultssupporting
confidence: 83%
“…Children with autistic spectrum disorders experience significant difficulties in recognizing various situations of Advances in Social Science, Education and Humanities Research, volume 298 interactionthis correlates to the results of R. Brewer's research which found that children with autism spectrum disorders experience difficulties not only in recognizing the emotions of other people, but also in expressing their own emotions [19,20].…”
Section: Discussionsupporting
confidence: 54%
“…This results in a disruption of the educational process (LaRocque et al 2011), the emergence of negative behaviors, a decrease in test and exam scores at school (Lei et al 2018), and decreased academic and nonacademic achievements (Dunifon et al 2013). These negative impacts are strong predictors for children wellbeing in the future (Rozental et al 2018;McMullen et al 2020).…”
Section: Introductionmentioning
confidence: 99%